Intra-individual joint angle variation during the take-off step of long jumpers with transtibial amputation - preliminary results - Funken, J.; Willwacher, S.; Heinrich, K.; Müller, R.; Hobara, H.; Grabowski, A. M.; Potthast, W. (ISBS Proceedings Archive (Michigan), 2019)
Biomechanical knowledge of the long jump take-off step is not comprehensive for athletes with below the knee amputation (BKA), yet it is important for improving training protocols and performance. Three-dimensional motion capture (Vicon) and a mathematical rigid-body model (Dynamicus, Alaska) were used to calculate joint angles during repeated long jump take-off steps of athletes with and without BKA. Preliminary results indicate that those athletes with BKA who perform better during the long jump compared to another athlete with BKA, have relatively high intra-individual joint angle variation at the knee and hip joint at the instant of take-off compared to non-amputee athletes. The presented results may stimulate future research questions and can inform athletes and coaches during the development of training protocols.